Association of SIRT1 (rs7069102) Gene polymorphism with premature myocardial infarction in young Egyptian patients - Altaher, Ali Mohamad; Foad, Amera Morad; Youssef, Wael; Ahmed, Ahmed Elsharawy (Egyptian Journal of Medical Human Genetics, 2024)
Background Premature myocardial infarction (PMI) is one of the most pressing global issues in modern cardiology. Recently, the incidence of PMI has gradually increased. Researches found that genetics is a major contributor in its development. SIRT1, an extremely conserved class III NAD-dependent deacetylase, has been linked to numerous cardiovascular disorders and engaged in a number of cellular functions. This work investigated the association between SIRT1 SNP rs7069102 in Egyptian patients ≤ 40 years old with premature ST-elevation Myocardial infarction (STEMI). Methods This cross sectional, single-center study included patients younger than 40 with STEMI (PMI group, n = 140) and a control group (n = 140) of healthy subjects of comparable age. In addition to clinical examination and standard tests, all participants underwent echocardiography, coronary angiography, SIRT1 (rs7069102) genotyping, and nitric oxide assay. Results The risk for PMI was increased in CG or CC genotype carriers of SIRT1 gene rs7069102 (OR: 3.93, 95% Cl: 2.25–6.86), as did carriers of the C allele (OR: 2.26, 95% Cl: 1.65–3.86). In the PMI group, endothelial nitric oxide synthase (eNOS) was significantly decreased; whereas, neuronal nitric oxide synthase (nNOS) was significantly increased. Conclusions SIRT1 single-nucleotide polymorphism (rs7069102) may confer an increased risk for PMI in young Egyptian patients with affecting endothelial nitric oxide synthase protein expressions. Traditional cardiovascular risk factors are prevalent in patients with PMI, with dietary behaviors, obesity, diabetes and dyslipidemia serving as independent risk factors for PMI. Clinical trial registration number : NCT05160844.